Compostagem orgânica e de resíduos de aves - (:unkn) unknown (Universidade Federal do Pampa, 2011)
Brazil is the leading country of exporting poultry meat according to the world ranking, with 3,1 million tons poultry meat exported in 2008 (USDA). Furthermore the country is the third largest producer of chicken meat. Yet every year, the Brazilian meat production increases. But along with this growth comes the amount of leavings generated. The AVIZOM (Association of Poultry Farmers in the Mata Zone) found that approximately each bird produces around 1, 4 kg of excrete; considering the average weight of 2 kg per bird, in 2009 around 7.7 million tones of excrete were produced in Brazil. CUNHA COELHO (2008) highlights the composting as a useful process to transform different types of organic leavings into compost, which, when added to soil, improves the physical, physical-chemical and biological characteristics. DAI PRA et al., (2005) defines composting as a system for birds carcasses disposal which solves a chronic problem of the modern poultry. This system is also useful for the correct placement of these animals waste. Therefore, the composting process (organic and poultry waste) enables the producer to a safe environmentally and economically viable placement of excrete and carcasses, in death cases. Based on these data, this study aims to review the different methods of composting, their importance and use, which can be an excellent option for these leavings disposal.
Keywords: Avicultura; Composteiras; Excretas; Resíduos orgânicos; Poultry; Poultry; Organic waste; CNPQ::CIENCIAS AGRARIAS